The effects of arthritis, mobility, and farm task on injury among older farmers - Reed D; Pickens H; Phillips JA; Azuero A; Heaton K (Dove Medical Press, 2012)
Karen Heaton1, Andres Azuero1, Jennan Phillips1, Herretta Pickens1, Deborah Reed21School of Nursing Birmingham, University of Alabama at Birmingham, AL, USA; 2College of Nursing, Lexington, KY, University of Kentucky, USAAbstract: The current study was conducted by performing secondary analysis of data drawn from a study of sustained work indicators of older farmers. The primary outcome variable was the reported occurrence or non-occurrence of injuries because of farm work in the past year. There were three explanatory variables of interest: (1) whether respondents reported ever having been diagnosed with arthritis/rheumatism by a medical doctor; (2) whether participants reported having mobility problems; and (3) a farm task injury risk index. Additional explanatory variables included the estimated number of days spent on farming activities in the past year, as well as demographic characteristics such as age, sex, and race. Institutional review board approvals were obtained for the original study prior to data collection, and for the current study prior to secondary analysis of data. Descriptive statistics were calculated for the outcome and explanatory variables. Initial multivariable longitudinal models for the occurrence of injuries were fitted with the explanatory variables. Odds ratios for the effects of interest were calculated using the final models. A longitudinal model was fitted using data in waves 1, 3, and 5, with a farm task injury risk index as outcome variable and wave, sex, age, race, and estimated number of days spent on farming activities in the past year as explanatory variables for exploration of the relationship between the farm task injury risk index and these variables. In this group of older farmers, aging was protective for injury, and was associated with decreased farm task injury risk index. Arthritis/rheumatism was associated in our study with occurrence of injury because of farm work across all four waves. Our results indicated that farmers with mobility problems were twice as likely to experience injuries because of farm work compared to farmers with no mobility problems. Increased farm task injury risk index was associated with a 40% increase in odds for the occurrence of injury due to farm work. In this study of older farmers, the type of work, and not the amount of work was significantly associated with injury risk. Implications for future studies of farm injury include the need for nurse researchers and others to incorporate objective validated measures of mobility and health care provider diagnoses of arthritis, and arthritis type. Nurse researchers should proceed with ongoing evaluation of the farm task injury risk index to determine its validity, reliability, and usefulness as a predictor of farm injuries. In the practice setting, nurses may apply findings from this study to provide injury prevention teaching to older farmers and their families. For example, discussions of the more risky farm tasks, injury prevention strategies, and treatment modalities including those that promote improved mobility should be targeted to older farmers with arthritis and actual or potential mobility issues. Ultimately, these nursing research and practice efforts may lead to preservation of function, and decreased injury risk and severity among older farmers.Keywords: aging, arthritis, mobility, farm injury